2021
DOI: 10.3390/cancers13153857
|View full text |Cite
|
Sign up to set email alerts
|

Non-Lynch Familial and Early-Onset Colorectal Cancer Explained by Accumulation of Low-Risk Genetic Variants

Abstract: A large proportion of familial and/or early-onset cancer patients do not carry pathogenic variants in known cancer predisposing genes. We aimed to assess the contribution of previously validated low-risk colorectal cancer (CRC) alleles to familial/early-onset CRC (fCRC) and to serrated polyposis. We estimated the association of CRC with a 92-variant-based weighted polygenic risk score (wPRS) using 417 fCRC patients, 80 serrated polyposis patients, 1077 hospital-based incident CRC patients, and 1642 controls. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Recent studies demonstrated that the polygenic background, defined as PRS based on disease-associated SNPs, modifies the risks for several cancers of the general population including CRC considerably, both in terms of age at onset and cumulative lifetime risks [ 12 , 23 , 27 , 36 38 ]. In line with this, the risk alleles of those SNPs are found to also accumulate in unexplained familial and early-onset CRC cases [ 25 , 39 ]. Whereas a low polygenic burden decreases the CRC risk down to one quarter on average, individuals with a high PRS (> 80%) doubles and those with a very high PRS (99%) almost quadruplicate their risk and thus, reach a CRC risk in an order of magnitude almost comparable to carriers of hereditary CRC with low PRS [ 31 ].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent studies demonstrated that the polygenic background, defined as PRS based on disease-associated SNPs, modifies the risks for several cancers of the general population including CRC considerably, both in terms of age at onset and cumulative lifetime risks [ 12 , 23 , 27 , 36 38 ]. In line with this, the risk alleles of those SNPs are found to also accumulate in unexplained familial and early-onset CRC cases [ 25 , 39 ]. Whereas a low polygenic burden decreases the CRC risk down to one quarter on average, individuals with a high PRS (> 80%) doubles and those with a very high PRS (99%) almost quadruplicate their risk and thus, reach a CRC risk in an order of magnitude almost comparable to carriers of hereditary CRC with low PRS [ 31 ].…”
Section: Discussionmentioning
confidence: 87%
“…As such, it is expected that the genetic background defined by the common risk variants may not only influence the occurrence of late-onset sporadic cases, but also modulate the risk of familial, early-onset, and hereditary CRC [ 25 ]. Recent studies demonstrated that high PRS values are associated with an increased risk of CRC and other common cancers in the general population up to an order of magnitude that is almost similar to hereditary tumor syndromes [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…We adjusted for family history, but participants with a history of familial CRC or one first degree relative younger than 60 would have been excluded from the CRC Screening Program and referred to the gastroenterologist. Thus, we do not have this population to study, but we have shown elsewhere that the PRS has a similar contribution in familial CRC [ 31 ]. Also, despite study participants were predominantly of European ancestry (97%), all the analyses were adjusted by five principal components obtained from the AIMS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that the polygenic background, de ned as PRS based on diseaseassociated SNPs, modi es the risks for several cancers of the general population including CRC considerably, both in terms of age at onset and cumulative lifetime risks [12,23,27,[35][36][37]. In line with this, the risk alleles of those SNPs are found to also accumulate in unexplained familial and early-onset CRC cases [25,38]. Whereas a low polygenic burden decreases the CRC risk down to one quarter on average, individuals with a high PRS (> 80%) doubles and those with a very high PRS (99%) almost quadruplicate their risk and thus, reach a CRC risk in an order of magnitude almost comparable to carriers of hereditary CRC with low PRS [31].…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is expected that the genetic background de ned by the common risk variants may not only in uence the occurrence of late-onset sporadic cases, but also modulate the risk of familial, early-onset, and hereditary CRC [25]. Recent studies demonstrated that high PRS values are associated with an…”
Section: Introductionmentioning
confidence: 99%